GROWTH, FIXED, AND MIXED MINDSETS: MINDSET SYSTEM PROFILES IN FOREIGN LANGUAGE LEARNERS AND THEIR ROLE IN ENGAGEMENT AND ACHIEVEMENT - Lou, Nigel Mantou; Chaffee, Kathryn Everhart; Noels, Kimberly A. (Studies in second language acquisition, 2022)
Language learners’ mindsets–their beliefs about whether language is a fixed aptitude that is immutable or a malleable capacity that can be developed–are associated with achievement goals, language-use anxiety, reappraisals of challenges, and persistence. This study integrates these mindset-related constructs to identify mindset-system profiles among foreign language learners. A latent profile analysis of 234 university students in foreign language courses revealed three distinct profiles. The fixed (21.8%) and growth (20.5%) profiles showed distinct and contrasting patterns of goals, reappraisals, anxiety, and persistence. However, most learners (57.7%) endorsed a mixed profile. Although mindsets alone did not predict grades, students in the growth profile were consistently most engaged and achieved the highest grades, suggesting that mindsets function as a system, in concert with related factors. This person-centered approach enhances our understanding of the complexity and functions of the mindset system, as well as the motivation of learners with mixed mindsets.